From opportunity seeking to gap filling: Reframing Brazil in Lusophone Africa - Seabra, P. (Brazil-Africa Relations in the 21st Century: From surge to downturn and beyond, 2021)
This chapter inquires whether Brazil’s headways in Africa over recent years were organic in nature and in content or, in fact, were achieved at the expense of other previously established actors. By reframing Brazil’s agenda towards African lusophone countries in juxtaposition to the perceived external downturn of Portugal, the propitious context and consequences of a new player on the continent can be best brought into evidence. The push-and-pull forces enacted by both Brazil and Portugal towards Lusophone Africa are explored through the aftermath of the 2012 military coup in Guinea-Bissau and the adhesion of Equatorial Guinea to the Community of Portuguese Language Countries (CPLP) in 2014. The chapter offers a reinterpretation of Brazil’s net gains in Africa and argues for its fragility and susceptibility to changing political-economic cycles.